2005
DOI: 10.1002/app.22598
|View full text |Cite
|
Sign up to set email alerts
|

The effects of excimer laser irradiation at 248 nm on the surface mass loss and thermal properties of PS, ABS, PA6, and PC polymers

Abstract: ABSTRACT:Excimer laser irradiation provides a new and important method for polymer surface treatment. In this work, the weight loss of engineering polymers PC, ABS, PS, and nylon 6 were investigated following irradiation by KrF excimer laser. The experimental results revealed that the polymeric weight loss is nonlinearly related to the laser energy and laser frequency for most of the materials tested. The effects of laser irradiation on the thermal properties (T g or T m ) of the polymers were investigated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Compared with polystyrene, the MMT has much higher absorption coefficient at k 5 248 nm (2.08-2.47 vs. 0.65 cm 21 ) and much lower specific heat (0.7996 vs. 1.647 J/gÁ C). [21][22][23][24] Therefore, more UV energy can be absorbed, and clay platelets are heated more efficiently resulting in accelerated photo-thermal ablation on PS chains. With increased number of clay platelets parallel to the specimen surface, more hot spots will be generated under UV irradiation, and consequently, more clay induced photo-thermal ablation will take place.…”
Section: Ablation Weight Lossmentioning
confidence: 99%
“…Compared with polystyrene, the MMT has much higher absorption coefficient at k 5 248 nm (2.08-2.47 vs. 0.65 cm 21 ) and much lower specific heat (0.7996 vs. 1.647 J/gÁ C). [21][22][23][24] Therefore, more UV energy can be absorbed, and clay platelets are heated more efficiently resulting in accelerated photo-thermal ablation on PS chains. With increased number of clay platelets parallel to the specimen surface, more hot spots will be generated under UV irradiation, and consequently, more clay induced photo-thermal ablation will take place.…”
Section: Ablation Weight Lossmentioning
confidence: 99%
“…After excimer-laser ablation of polymer films, the film thickness can be readily reduced and varied by controlling the ablation conditions such as fluence and repetition rate, due to the photochemical etching effect of the excimer laser. [26] The concave PS cylinders of untreated SIS + PS12k (Fig. 2b, depth ca.…”
Section: Full Papermentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) is a biodegradable polymer, and it can be blended with starch to produce biodegradable polymeric films, and there are scanty studies on the degradation of the biodegradable blends in various environmental conditions . Laser and γ‐ray radiation along with natural weathering can be used to study the degradation of polymers . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Laser and g-ray radiation along with natural weathering can be used to study the degradation of polymers. [9][10][11] Zhang et al [9] studied the effect of g-ray radiation on the degradation nature of PVA in aqueous solutions. They found that efficiency of degradation of PVA depends upon dose rate, PVA concentration and the amount of additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation